2019
DOI: 10.3390/ma12233918
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach of Mathematical Analysis of Structure of Graphene as a Potential Material for Composites

Abstract: The new analysis of a simplified plane model of single-layered graphene is presented in this work as a potential material for reinforcement in ultralight and durable composites. However, owing to the clear literature discrepancies regarding the mechanical properties of graphene, it is extremely difficult to conduct any numerical analysis to design parts of machines and devices made of composites. Therefore, it is necessary to first systemize the analytical and finite element method (FEM) calculations, which wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Hence, in order to ensure proper silanization when adding HAp, it is necessary to consider its amount and morphology, as well as to increase the amount of pre-adhesive (silanizing) agents modifying the surface, as demonstrated previously [ 52 ]. Another solution that may improve the mechanical properties is to introduce additives that block the propagation of composite matrix cracking (e.g., graphene), which should also improve the properties of dental composites [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in order to ensure proper silanization when adding HAp, it is necessary to consider its amount and morphology, as well as to increase the amount of pre-adhesive (silanizing) agents modifying the surface, as demonstrated previously [ 52 ]. Another solution that may improve the mechanical properties is to introduce additives that block the propagation of composite matrix cracking (e.g., graphene), which should also improve the properties of dental composites [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…All models are constructed based on a (6 × 6) graphene supercell with metal and nitrogen dopants. The supercell has dimensions of 14.76 Å × 14.76 Å × 15 Å, which is in line with previous reports . A Monkhorst–Pack 2 × 2 × 1 k -point mesh is applied for integrating the Brillouin zone.…”
Section: Methodsmentioning
confidence: 99%
“…The supercell has dimensions of 14.76 Å × 14.76 Å × 15 Å, which is in line with previous reports. 38 A Monkhorst−Pack 2 × 2 × 1 k-point mesh is applied for integrating the Brillouin zone. The cutoff energy is set to 400 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It was shown that the appropriate selection of silane for the appropriate fraction of the filler improved the mechanical properties of the composite [35]. An alternative may also be the introduction of other additives, which could improve the properties of dental composites by blocking the propagation of composite matrix cracking (e.g., graphene) [36]. However, it should be borne in mind that adding more than 5% of silane to composites causes the surface to become rougher and nonhomogeneous [37,38], which can significantly reduce the wear resistance.…”
Section: Wear Resistance Testmentioning
confidence: 99%